Synthetic Turfgrass and the Nine Principles of Florida-Friendly Landscaping™ - Jason Kruse; Bryan Unruh; Jennifer Marvin; Tom Wichman; Lynn Barber; Norma Samuel; John Bossart; Claire Lewis; Esen Momol (EDIS)
Synthetic turf is a manufactured product that utilizes synthetic fibers that mimic the aesthetic look of natural grass. While designed to imitate the look of natural turf, synthetic turf does not provide the ecosystem benefits of a natural turf system. This publication examines the properties of synthetic turf in relation to each of FFL’s nine principles. A new publication of the UF/IFAS Environmental Horticulture Department; 4 pages. https://edis.ifas.ufl.edu/ep612